2013
DOI: 10.1002/ejic.201300151
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Complexes of Bipyrrolidine‐Based Diamine‐Diphenolato and Diamine‐Diolato Ligands: Predetermination of Helical Chirality Around Tetrahedral Centres

Abstract: The coordination chemistry of chiral tetradentate dianionic ligands of the diamine-diphenolato and diamine-diolato families having the (R,R)-2,2Ј-bipyrrolidine core around Zn II was investigated. Reactions with diethylzinc led to complexes of the type [{ONNO}Zn] for most ligands and to bridging dinuclear complexes of the type [μ-Lig 4 (ZnEt) 2 ] for one of the diamine-diolato ligands. Reactions with bis(hexamethyldisilazide)zinc led to complete conversions. Most complexes were obtained as mononuclear complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…We observed the same diastereoselectivity with an ( S , S )‐configured bis(pyrolidine) salan ligand, that resulted exclusively in the Λ‐configured Mo complex . However, in some cases the formation of both diastereomers of Zn and Ti complexes were observed, even if enantiopure salan ligands were used , , . Furthermore, a molybdenum(VI) complex was reported, that gave a 1:1 mixture of diastereomers when a chiral salalen ligand (only one imine moiety reduced to the corresponding amine) was used …”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…We observed the same diastereoselectivity with an ( S , S )‐configured bis(pyrolidine) salan ligand, that resulted exclusively in the Λ‐configured Mo complex . However, in some cases the formation of both diastereomers of Zn and Ti complexes were observed, even if enantiopure salan ligands were used , , . Furthermore, a molybdenum(VI) complex was reported, that gave a 1:1 mixture of diastereomers when a chiral salalen ligand (only one imine moiety reduced to the corresponding amine) was used …”
Section: Resultssupporting
confidence: 58%
“…Such high diastereoselectivities were also observed for other ( R , R )‐enantiopure salan ligands like H 4 L 2 , leading to the Δ‐configuration at the molybdenum atom . Kol and co‐workers reported similar behavior for titanium(IV) complexes, and could also show that the ( S , S )‐configured cyclohexyldiamine ligand gives the opposite Λ‐configuration at the metal atom , , …”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…We and others have previously demonstrated that {ONNO}type tetradentate-dianionic ligands assembled around the chiral-2,2'-bipyrrolidine core tend to wrap diastereoselectively around different metals. [19][20][21][22][23] In contrast, aluminum complexes of salan ligands assembled around the chiral diaminocyclohexane core were obtained as mixtures of diastereomers which led to low levels of stereocontrol in rac-a nd meso-lactide polymerization. [24] Aiming at higher stereoselectivity while not retarding reactivity, [25,26] we targeted two new ligand precursors:t he C 2 -symmetric Lig 1 H 2 bearing ortho-phenyl substituents on the two phenolates,and the hybrid C 1 -symmetric Lig 2 H 2 bearing an ortho-phenyl phenolate and a2 ,4-dichlorophenolate (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…hexane core,t hey led to single diastereomers of predetermined chirality of the Ndonors when wrapping around octahedral Group 4t ransition-metal centers as well as around tetrahedral zinc centers. [17,18] We hypothesized that such ahigh diastereoselectivity would be attained around the pentacoordinate aluminum as well.…”
mentioning
confidence: 99%